The effects of nutrition and reproductive strategies on performance of beef cattle grazing native shortgrass range in western Kansas - Bennett, Bradley Wayne (Kansas State University, 2013)
Cattle grazing dormant native range (< 7% crude protein; CP) require supplementation of additional protein to sustain body weight (BW) and body condition score (BCS). Daily delivery of these supplements is an economic burden to cattle producers faced with challenging economic circumstances. Supplementing cows infrequently (as little as once/week) has produced equivalent BW and BCS changes compared to daily delivery. Dried distiller’s grains with solubles (DDGS) provides more ruminally-undegradable protein (RUP; 50-60%) compared to traditional oilseed-meal supplements (i.e. soybean meal) that are >50% ruminally-degradable protein (RDP). Therefore, our objective was to evaluate the effects of supplementation frequency on performance, reproductive success, eating behavior, and subsequent calf performance of spring-calving cows supplemented with DDGS. No differences in ending BW (P = 0.69) and BCS (P = 0.49), or changes in BW and BCS over the supplementation period (P = 0.82 and 0.70, respectively) were observed among cows supplemented every d, every 3 d, or every 6 d. Calf BW at birth, weaning weight (WW), and average daily gain (ADG) were similar among treatments (P = 0.19, 0.12, and 0.10, respectively). First-service conception rate (FSCR) and final pregnancy rate (PR) were also not affected by supplementation frequency (P = 0.62 and 0.76, respectively). The development of replacement heifers is a large expense for cow-calf producers. Improved breeding and heifer development strategies aimed at ensuring the success of replacement females have been developed but reproductive failure still remains a problem. The stress associated with breeding and handling procedures may decrease reproductive success. Therefore, the objective was to determine if intramuscular administration of flunixin meglumine (1.1 mg/kg BW) 14 days post-breeding would improve FSCR and PR in non-transported replacement heifers. Under the conditions of our study, flunixin meglumine did not improve (P = 0.87) first service conception rate above that of control heifers (41.2% and 42.3%, respectively). Final pregnancy rate also was not different between treatments and averaged 81.8% (P = 0.40).
Keywords: Supplementation frequency; Dried distiller's grains; Flunixin meglumine; Beef cows; Beef heifers; Animal Sciences (0475)